The Virtue of Maintaining Ties of Kinship as a Solution to Overcoming the Phenomenon of Individualism: Study of Takhrij Hadith - Salsabila, Syifa Sahla; Fauzi, Ridwan (Faculty of Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
The purpose of this study is to analyze the hadith on the virtue of maintaining ties of kinship as a solution to addressing the phenomenon of individualism. This research employs a qualitative approach using a literature study method. The formal object of this study is hadith studies, while the material object is the hadith on the virtue of maintaining ties of kinship as narrated in Bukhari No. 5527. The findings and discussion indicate that the hadith is classified as hasan li ghairihi, meeting the qualifications of maqbul ma’mul bih for Islamic practice. This study concludes that the hadith narrated by Bukhari No. 5527 is relevant as a solution to overcoming the growing phenomenon of individualism in society.